2023
DOI: 10.1002/jmv.29072
|View full text |Cite
|
Sign up to set email alerts
|

Infection with COVID‐19 is no longer a public emergency: But what about degenerative dementia?

Burak Yulug,
Behçet Ayyıldız,
Sevilay Ayyıldız
et al.

Abstract: Although no longer considered a public health threat, post‐COVID cognitive syndrome continues to impact on a considerable proportion of individuals who were infected with COVID‐19. Recent studies have also suggested that COVID may be represent a critical risk factor for the development of Alzheimer's disease (AD). We compared 17 COVID patients with 20 controls and evaluated the effects of COVID‐19 on general cognitive performance, hippocampal volume, and connections using structural and seed‐based connectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Reduced connectivity between the right head of hippocampus and regions of the dorsal attention network was observed in non-hospitalized patients with long-COVID compared to healthy controls approximately eleven months after the infection ( Díez-Cirarda et al, 2023 ). In contrast, another study reported enhanced connectivity between subfields of the hippocampus and other regions of the (para)limbic network in recovered COVID-19 patients ( Yulug et al, 2023 ).…”
Section: Resultsmentioning
confidence: 91%
“…Reduced connectivity between the right head of hippocampus and regions of the dorsal attention network was observed in non-hospitalized patients with long-COVID compared to healthy controls approximately eleven months after the infection ( Díez-Cirarda et al, 2023 ). In contrast, another study reported enhanced connectivity between subfields of the hippocampus and other regions of the (para)limbic network in recovered COVID-19 patients ( Yulug et al, 2023 ).…”
Section: Resultsmentioning
confidence: 91%
“…Furthermore, previous cognition studies of depressive patients have primarily focused on alterations in the hippocampus, amygdala, and cingulate gyrus, without considering functional alterations in other critical subcortical structures, such as the thalamus, and especially the pulvinar 14 . Such alterations may indicate a critical dynamic phase associated with subtle pathophysiological changes occurring before the manifestation of structural changes 15–17 . From that perspective, functional connectivity analysis is a valuable method for examining voxel‐wise functional magnetic resonance imaging (MRI) signals and that identifies functionally related brain areas and distributed networks.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Such alterations may indicate a critical dynamic phase associated with subtle pathophysiological changes occurring before the manifestation of structural changes. 15 , 16 , 17 From that perspective, functional connectivity analysis is a valuable method for examining voxel‐wise functional magnetic resonance imaging (MRI) signals and that identifies functionally related brain areas and distributed networks. This therefore justifies an investigation of the differences between amnestic and other depressed individuals.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, research has failed to find a specific marker of neuroinflammation, 67 or structural alterations were not found in other samples. 48,62 As with functional alterations, the severity of the acute episode and the presence of persistent symptoms are more closely related to structural alterations, primarily in white matter integrity. 66,68…”
Section: Discussionmentioning
confidence: 99%
“…Most studies investigating functional brain activity in patients recovered from COVID-19 have been conducted using resting-state methods. Alterations in signal properties and functional connectivity have been found in COVID-19 patients, 55,56 and have been associated with hospitalization, 57 and persistent symptoms such as headaches, 58 persistent olfactory dysfunction 48,59,60 and other behavioral markers such as working memory performance, 61,62 anxiety, 63 psychotic-like experiences in adolescents, 64 and post-traumatic stress symptoms. 65 Also, some studies found no functional alteration in recovered COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%